UJI ORGANOLEPTIK SELAI BUAH SALAK (Salacca edulis REINW) BERDASARKAN PENAMBAHAN GULA - Nurmiati Asmar Suneth; Prelly M.T Tuapattinaya (BIOPENDIX, 2016)
Background: Salak is one of Indonesia's native tropical fruit crops and is one of the interesting commodities to be developed to meet domestic and export needs. Salak can be processed foods such as salak jam. Method: This research was conducted on March 8-16, 2016. This research use descriptive research type. The parameters measured and observed are the color, texture, taste, and level of fondness. Results: The results showed that the higher the sugar addition, the higher the organoleptic value, the highest degree of the sensitivity to the color, texture, and taste was on the 100 gram sugar treatment and the lowest on the 0 gram sugar treatment. Conclusion: Based on the results of the study can be concluded that the addition of sugar has an effect on organoleptic quality of fruit jam.